Improved degradation of diuron herbicide and pesticide wastewater treatment in a three-dimensional electrochemical reactor equipped with PbO2 anodes and granular activated carbon particle electrodes. (1st November 2021) - Rahmani, Alireza; Leili, Mostafa; Seid-mohammadi, Abdolmotaleb; Shabanloo, Amir; Ansari, Amin; Nematollahi, Davood; Alizadeh, Saber
Abstract: The electrocatalytic performance of porous carbon felt/PbO2 and planar titanium/PbO2 anodes in a three-dimensional electrochemical reactor (3DER) equipped with granular activated carbon (GAC) particle has been studied for synergistic degradation of diuron herbicide (DIU) and treatment of pesticide wastewater. The results showed that porous carbon felt/PbO2 anode in addition to high stability can provide around three times more surface area than titanium/PbO2 for degradation reactions. Optimization of DIU degradation in 3DER system with carbon felt/PbO2 anode was performed by a five-level rotatable central composite design. The TOC mineralization rate under optimal conditions (pH = 4.7, current density = 13.5 mA cm −2, Na2 SO4 concentration = 0.04 M and DIU concentration = 40 mg L −1 ) for the 3ٍِDER system with carbon felt/PbO2 and titanium/PbO2 anodes after 50 min were 100% and 63.8%, respectively. However, the electrocatalytic efficiency of carbon felt/PbO2 and titanium/PbO2 anodes in the absence of GAC particles to remove TOC was 85.5 and 42.7%, respectively. The energy consumed in the 3DER system equipped with carbon felt/PbO2 anode was 2.28 times less than the 3DER system with titanium/PbO2 . The contribution of direct and indirect oxidation of DIU in 3DER degradation systems was determined by radical scavenging technique. The safety of the anodes was evaluated for Pb 2+ leakage. The DIU degradation pathway was proposed based on the intermediates identified by LC-MS. The performance of optimized 3DER systems was evaluated for treatment of real pesticide wastewater. The chemical oxygen demand (COD) removal efficiency after 300 min of reaction in the 3DER system with carbon felt/PbO2 and titanium/PbO2 electrodes was 95% and 62.5%, respectively. Graphical abstract: Image 1 Highlights: Electrocatalytic synergy of the porous carbon felt/PbO2 anode and GAC particle electrode for diuron herbicide degradation. Direct and indirect oxidation of diuron in 3DER systems. Complete removal of TOC in 3DER system with carbon felt/PbO2 . The lowest leaking of Pb 2+ into the sample solution was found in the 3DER system with carbon felt/PbO2 anode. Real pesticide wastewater treatment with 3DER systems.